A review of III–V nanowire infrared photodetectors and sensors. (16th February 2017) - LaPierre, R R; Robson, M; Azizur-Rahman, K M; Kuyanov, P
Abstract: A review of III–V nanowire-based infrared photodetectors is provided including single nanowires, ensemble nanowires, and heterostructured nanowires. The performance metrics of reported nanowire photodetectors are compared. The potential advantages of nanowire photodetectors, including enhanced absorption, fast carrier collection, multispectral detection, and direct growth on Si, are discussed.